Effect of Probiotics Lactobacillus acidophilus on Citrobacter rodentium Colitis: The Role of Dendritic Cells - CHEN, CHIEN-CHANG (2009)
Modulation of the intestinal immune response early in life by administration of probiotic bacteria may be an effective strategy for preventing or attenuating infectious diarrhea. We preinoculated the mice early in life with the probiotic bacteria Lactobacillus acidophilus NCFM (La) at age 2 wk. Dendritic cells (DCs) were collected and purified from mesenteric lymph nodes (MLN) and spleens of the BalbC/ByJ mice. DC isolation and adoptive transfer was used to examine the function of probiotics. We demonstrated that when mice were adoptively transferred with La-primed DCs (t-LaDC) instead of oral consumption with La, there was a similar effect on fecal bacteria counts, IgA levels, and colonic histopathology, as well as cytokine levels in MLN when there was intestinal bacterial infection. The above findings suggest that DCs play a key role in probiotics attenuating Citrobacter rodentium (Cr) colitis. Moreover, the location of La-primed DC hints that there is interaction of DCs and T cells in the digestive system of the host. Up-regulated expression of a surface marker on DCs indicated that inoculation with probiotics will stimulate the function of DCs, thereby further increasing immune response triggered by DC.